The Glasgow Prognostic Score Determined During Concurrent Chemoradiotherapy Is an Independent Predictor of Survival for Cervical Cancer. Issue 7 (September 2015) - Nishida, Takeshi; Nakamura, Keiichiro; Haraga, Junko; Ogawa, Chikako; Kusumoto, Tomoyuki; Seki, Noriko; Masuyama, Hisashi; Katayama, Norihisa; Kanazawa, Susumu; Hiramatsu, Yuji
Abstract : Objective: The Glasgow prognostic score (GPS) determined at pretreatment is important in the prediction of prognosis in various cancers. We investigated if the GPS used both at pretreatment and during concurrent chemoradiotherapy (CCRT) could predict the prognosis of patients with cervical cancer. Methods: We collected GPS and clinicopathological data from the medical records of 91 patients who underwent CCRT for cervical cancer; their GPSs at pretreatment and during CCRT were retrospectively analyzed for correlations with recurrence and survival. Statistical analyses were performed using the Mann-Whitney U test. Disease-free survival (DFS) and overall survival (OS) were analyzed using the Kaplan-Meier method. Cox's proportional hazard regression was used for univariate and multivariate analyses. Results: The median follow-up for all patients who were alive at the time of last follow-up was 38.0 months (range, 1–108 months). The DFS and OS rates of patients with a high GPS during CCRT (GPS 1 + 2; 55 patients; 60.4%) were significantly shorter than those for patients with a low GPS (GPS 0; 36 patients; 39.6%) (DFS, P < 0.001; OS, P < 0.001). Furthermore, multivariate analyses showed that high GPS during CCRT was an independent prognostic factor of survival for OS ( P = 0.008). Conclusions: During CCRT, a high GPS was revealed to be an important predictor of survival for cervical cancer.